Changes in the stress field after the 2008 M7.2 Iwate‐Miyagi Nairiku earthquake in northeastern Japan. Issue 12 (28th December 2014) - Yoshida, Keisuke; Hasegawa, Akira; Okada, Tomomi; Iinuma, Takeshi
Abstract In order to investigate changes in the stress field following the 2008 M7.2 Iwate‐Miyagi Nairiku earthquake in NE Japan, we determined many focal mechanisms within the focal area, using data from both the dense aftershock observation network deployed just after the main shock and other temporary and routinely operated stations in the surrounding area. Applying stress tensor inversions to these focal mechanism data, we estimated the detailed spatial distribution of the principal stress orientations in this event's source area. Estimated orientations of the maximum principal stress (σ1) axes differ significantly before and after the main shock. Before the main shock, the σ1 axis is oriented WNW‐ESE across the entire studied area, which is parallel to the plate convergence direction. After the main shock, however, the orientation of the σ1 axis changed significantly and showed remarkable spatial variation. In the northern and southern parts of the aftershock area, located relatively far from the main shock large slip area, the σ1 axes are oriented WNW‐ESE, similar to those before the main shock. In contrast, to the east and west of the central part of the aftershock area, the σ1 axes are oriented N‐S and NE‐SW, respectively. This characteristic spatial pattern of σ1 axis orientations is approximately consistent with that of static stress change associated with the main shock rupture, which strongly suggests that the spatially heterogeneous stress after the main shock is caused by such static stress change. The differential stress magnitude before the main shock is estimated to be less than 10–30 MPa, suggesting that the main shock faults are weak.